Hubungan Pola Asuh Orangtua Terhadap Pertumbuhan dan Perkembangan Anak dengan Autism - Yena Wineini Migang (STIKes Hang Tuah Pekanbaru, 2017)
Abstract Relationship Parenting of Parents on Growth and Development of Children with Autism Background: Autism is a developmental disorder of the nervous system to someone who is mostly caused by heredity and sometimes have been detected since the baby is 6 months old. Parenting parents are also needed in the stage of growth and development, for the most time interaction of children with autism in the family. Parents act as a stimulator of growth and development of children with autism. Methods: the cross-sectional study, with bivariate Spearman rho test. the number of samples of 84 children with autism and their parents in the city of Palangka Raya, sampling with purposive sampling techniques, data collection using observation sheets, questionnaires and WHO Anthro software plus 2011. Results: The pattern of the highest parenting, parenting democratic (84.5%), permissive parenting (8.3%), parenting authoritative (7.1%). The nutritional status of children with autism is the highest percentage of normal nutritional status (53.6%), the nutritional status of obese (21.4%), the nutritional status of obesity (17.9%), nutritional status and very thin respectively at (3.6%). Cognitive level autism, the highest percentage increase cognitive level (73.8%), and the degree of cognitive and equipment (26.2%). There is a significant relationship with parenting parents with nutritional status of children with autism, where the value of Ï 0.008> Î± 0.01. There is a relationship between parenting significant mother with autism Ï cognitive level of 0.001> Î± 0.01. Conclusion: It should be investigated other factors that cause nutritional status of children with autism can become obese even there is a very thin, so that even children with autism have to diet gluten and casein, as a condition of early treatment of children with autism, they can still have a normal nutritional status, and did not experience obesity due to food composition that is not observed. Parents need to determine the appropriate parenting as a medium of interaction with autistic children, because children with autism who have problems communicating will be difficult to receive information from the environment as, which means it will be difficult to increase the cognitive learning and would be difficult anyway receive the diet as a non-medical treatment of children with autism. Keywords: Pattern foster parent, cognitive, nutritional status, children with autism